SUBJECTIVITY AND RESPONSIBILITY AS A SYSTEMICALLY IMPORTANT PARAMETERS OF LIFE CREATION ACTIVITY OF PERSONALITY - Yamnytsky, Vadym (PSYCHOLOGICAL JOURNAL, 2016)
The article presents the author's approach to the theoretical solution of the problem of development of Life Creation activity. Life Creation of Person is considered as a process of the implementation of targeted and meaningful aspects of their own lives, regulated by motivation redundancy on the basis of the integrity of the manifestation of the adaptive, creative and subjective activity. The Phenomenology of Life Creation covers a wide problem’s space which has three dimensions: the potential (Personslity crisis), Actual (Life Creation), Boundary (meta-activity level, another kind of being). The Potential level of regulation suggests the development process of Life Creation by individual experiences of appropriate type of crisis. The Actual level suggests the existence of differences between Life Creation types identity and distinguish Life Creation respectively, oriented to Adaptation, to Creation or to the development of the Subject (self). The Boundary level is possible on the basis of Actual implementation in full and characterized by the implementation of own uniqueness in the form of Culture Creation.